Removal of chromium (VI) from aqueous solution using Eggshell/ poly pyrrole composite - Saied Ehsanpour; Majid Riahi Samani; Davood Toghraie (Alexandria Engineering Journal, 2023)
In this study, eggshell/poly pyrrole composites were investigated to remove chromium (VI) from the aqueous medium. Chromium removal experiments were performed as a batch reactor and parameters such as contact time, pH of chromium solution, and the amount of adsorbent consumed and adsorption isotherms were examined. Scanning electron microscopes (SEM), Fourier transform infrared (FTIR) and X-ray diffraction (XRD) techniques were also used to characterize the adsorbent. The results of this study indicated that eggshell/poly pyrrole composites could have a favorable effect on the removal of chromium from the aqueous medium. Eggshell/poly pyrrole composite that was prepared in the presence of 2 gr/l Poly Ethylene glycol in a mixture of water and ethanol solvents as an adsorbent showed the highest removal efficiency with more than 80 % adsorption in chromium removal. The optimal chromium removal time for this composite was 30 min and the highest removal percentage was observed at acidic pH = 5. For eggshell/poly pyrrole composite that is prepared in the presence of 2 gr/l Poly Ethylene glycol in water/ethanol solvent, the adsorption process followed by Langmuir and Freundlich isotherms and the maximum amount of chromium adsorption per unit mass of the prepared composite was equal to175.5 mg/ gr.